Physical culture and sport as factors of socializations to personality - Mamaeva E.V.; Mamaev D.Y. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
The analysis of publications is resulted on the topic of research. Essence of physical culture and sport is exposed and its place is certain in the system of public relations. The socializing function of sport is considered. Pedagogical facilities of forming personality of sportsman are exposed. A few determinations of concept of socialization are given. The basic institutes of socialization are presented. Influence of physical culture and sport is investigational on the process of socialization of personality. It is well-proven that efficiency of socialization in sport depends on the level of coincidence of values of sport and values of society and personality.